A New Methodology for Assessing Macromolecular Click Reactions and Its Application to Amine–Tertiary Isocyanate Coupling for Polymer Ligation - Gody, Guillaume; Roberts, Derrick A; Maschmeyer, Thomas; Perrier, Sébastien (Journal of the American Chemical Society, 2016)
Click reactions have provided access to an array of remarkably complex polymer architectures. However, the term “click” is often applied inaccurately to polymer ligation reactions that fail to respect the criteria that typify a true “click” reaction. With the purpose of providing a universal way to benchmark polymer–polymer coupling efficiency at equimolarity and thus evaluate the fulfilment of click criteria, we report a simple one-pot methodology involving the homodicoupling of α-end-functionalized polymers using a small-molecule bifunctional linker. A combination of SEC analysis and chromatogram deconvolution enables straightforward quantification of the coupling efficiency. We subsequently employ this methodology to evaluate an overlooked candidate for the click reaction family: the addition of primary amines to α-tertiary isocyanates (α- t NCO). Using our bifunctional linker coupling strategy, we show that the amine– t NCO reaction fulfills the criteria for a polymer–polymer click reaction, achieving rapid, chemoselective, and quantitative coupling at room temperature without generating any byproducts. We demonstrate that amine– t NCO coupling is faster and more efficient than the more common amine–tertiary active ester coupling under equivalent conditions. Additionally, we show that the α- t NCO end group is unprecedentedly stable in aqueous media. Thus, we propose that the amine– t NCO ligation is a powerful new click reaction for efficient macromolecular coupling.